PENGARUH PENDEKATAN ETNOSAINS DALAM PEMBELAJARAN IPA DI SEKOLAH DI TINJAU DARI FILSAFAT ILMU - Loly Suwandani; Sudjarwo Sudjarwo; Tri Jalmo (Bajang Institute, 2022)
This study is a meta-analysis study that aims to determine the effect of the ethnoscience approach in science learning in schools in terms of the philosophy of science. This study integrates the results of primary studies from several studies that have been published in national and international journals. The method used in this study is an analysis of the results of 9 international journals and 1 national journal which involves the influence of the ethnoscience approach in science learning as the main study. The search was conducted through the Google search engine, using Google Scholar and Semantic Scholar with the keywords influence of ethnoscience approach. Data analysis used the average effect size of each research sample which was then categorized based on Cohen's interpretation. The results of the study indicate that the use of the ethnoscience approach in science learning is very influential with a large effect size of 1.59. The influence of the ethnoscience approach is based on the field of study and level of education. So it can be concluded that there is a significant effect on the use of the ethnoscience approach in learning science in schools.